MENANYA EKSISTENSI TUHAN DALAM BENCANA - Derry Cristofer (Jurnal Euntes, 2023)
Disasters and human life seem to be two things that are inseparable from one another. In the history of human life, disasters come and gone, starting from a small scale to a large extent. Religious people tend to see the reality of this disaster as part of God’s plan for humans or it can be seen as God’s punishment for humans. Meanwhile, scientists view disasters rationally. Disasters have always been seen as part of a natural cycle that can occur either due to human activities or natural factors. This paper will focus on the theological views on disasters. The author specifically examined the ever-asking question when humans face disasters, namely the existence of God in disasters. Through a qualitative method with literature analysis and reflection enrichment, the writer tries to answer questions about God’s plan in disasters.